Pengaruh Bauran Pemasaran, Keunggulan Bersaing, terhadap Keputusan Berobat untuk Meningkatkan Loyalitas Pasien di Rumah Sakit X, Jakarta Selatan - Muhammad Jayuli; Endang Ruswanti; Wahyuni Dian Purwati (Syntax Corporation Indonesia, 2022)
Currently the competition in the hospital business industry is very fierce. Every hospital must require to compete their service and price. Therefore, the hospital must have the good business strategy to survive and get margin. This study was to examine the effect of the 4P marketing mix and competitive advantage, on intention to seek treatment and its relationship with patient loyalty at Halimun Hospital, Jakarta. We use 67 patients the sample were inpatient and outpatient between July to September 2020 in Halimun Hospital. We calculate the data analysis using path test (Path Analysis), the result showed a significant influence between the 4P marketing mix variable, competitive advantage with patient desires for treatment and patient loyalty. The research finding is that the subjective norm of the location and promotion marketing mix variables has the most influence on treatment intentions to encourage patient loyalty